2002
DOI: 10.1046/j.1365-3040.2002.00879.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth temperature influences the underlying components of relative growth rate: an investigation using inherently fast‐ and slow‐growing plant species

Abstract: We examined the effect of growth temperature on the underlying components of growth in a range of inherently fast-and slow-growing plant species. Plants were grown hydroponically at constant 18, 23 and 28 °°°° C. Growth analysis was conducted on 16 contrasting plant species, with whole plant gas exchange being performed on six of the 16 species. Inter-specific variations in specific leaf area (SLA) were important in determining variations in relative growth rate (RGR) amongst the species at 23 and 28 °°°° C bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
200
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(224 citation statements)
references
References 47 publications
20
200
1
3
Order By: Relevance
“…In the present study, warming appeared to increase the specific leaf area (SLA) of the two conifer species under the 60-year plantation, which could allow seedlings to harvest light more effectively under low-light conditions. The results were in agreement with that of Loveys et al (2002), who reported increases in SLA with increasing growth temperature for some fast-growing plant species. In contrast, Lemmens et al (2006) observed no temperature effects on SLA.…”
Section: Photosynthetic Parameters Treatmentsupporting
confidence: 92%
“…In the present study, warming appeared to increase the specific leaf area (SLA) of the two conifer species under the 60-year plantation, which could allow seedlings to harvest light more effectively under low-light conditions. The results were in agreement with that of Loveys et al (2002), who reported increases in SLA with increasing growth temperature for some fast-growing plant species. In contrast, Lemmens et al (2006) observed no temperature effects on SLA.…”
Section: Photosynthetic Parameters Treatmentsupporting
confidence: 92%
“…Furthermore, SLA is considered to be one of the most important factor driving variation in plants relative growth rate as well as the photosynthetic ability . The result suggested that these seedlings had a greater ability to capture light more effectively, which is consistent with one previous study (Loveys et al, 2002).…”
Section: Night Warming Effect On Photosynthesis In Late Growing Seasonsupporting
confidence: 92%
“…Photosynthetic acclimation is relatively small in preformed leaves and larger in leaves that develop at the lower temperature (Strand et al, 1997;Campbell et al, 2007;Atkinson et al, 2010). The process includes an increase in leaf thickness and the overall protein concentration (Strand et al, 1999;Tjoelker et al, 1999;Loveys et al, 2002;Campbell et al, 2007). The latter is at least partly due to a decrease in vacuole size allowing the cytoplasm to occupy a larger proportion of the cellular volume (Huner et al, 1981;Griffith et al, 1985;Strand et al, 1999).…”
Section: Introductionmentioning
confidence: 99%